Glaube Hoffnung Liebe Tot - Graphische Sammlung Albertina, Wien; Kunsthalle Wien; Anders, Günther; Badura-Triska, Eva; Barasch, Moshe; Belting, Hans; Besset, Maurice; Bickers, Patricia; Bina, Griese; Birnbaum, Dara; Bouisset, Maïten; Bourdon, David; et al. (Klagenfurt : Ritter Verlag, 1995)
Antoni, Janine ; Arrowsmith, Sue ; Bacon, Francis ; Baldessari, John ; Beckman, Ford ; Bellmer, Hans ; Beuys, Joseph ; Birnbaum, Dara ; Blume, Bernhard Johannes ; Brauntuch, Troy ; Brus, Günter ; Bunuel, Luis ; Burden, Chris ; Cahn, Miriam ; Cerminova, Toyen / Marie ; Christo & Jeanne-Claude ; Dine, Jim ; Duchamp, Marcel ; Export, Valie ; Fend, Peter ; Fontana, Lucio ; Francis, Sam ; Gerz, Jochen ; Gober, Robert ; Golub, Leon ; Gormley, Antony ; Haider, Ilse ; Hammons, David ; Holzer, Jenny ; Kelley, Mike ; Klein, Yves ; Man Ray ; Mendieta, Ana ; Messager, Annette ; Morris, Robert ; Nauman, Bruce ; Newman, Barnett ; Nitsch, Hermann ; Oppenheim, Meret ; Oroschakoff, Haralampi G. ; Orozco, Gabriel ; Pane, Gina ; Puckey, Thom ; Quinn, Marc ; Rainer, Arnulf ; Rauschenberg, Robert ; Rinke, Klaus ; Schaerf, Eran ; Schwarzkogler, Rudolf ; Serrano, Andres ; Simotová, Adriena ; Smithson, Robert ; Spero, Nancy ; Thek, Paul ; Turrell, James ; Viola, Bill ; Warhol, Andy ; Williams, Sue ; de Maria, Walter
biog. p. 492-493, Autoren p. 494, Autoren der Reprints, Quellen p. 495
Glaube Hoffnung Liebe Tot, Kunsthalle Wien, 14.12.1995 - 31.01.1996 ; Graphische Sammlung Albertina, Wien
Duits
kunstcatalogus